2021
DOI: 10.1590/1807-3107bor-2021.vol35.0121
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and effect of TiF4 on dental caries: a randomized controlled clinical trial

Abstract: This randomized three-armed controlled clinical trial compared the effect of titanium tetrafluoride (TiF 4 ) and sodium fluoride (NaF) varnishes on caries control in smooth surfaces of permanent dentition and children's acceptability. Sixty children (6-8 y/o) were randomly divided into TiF 4 (2.45% F -), NaF (2.26% F -) or placebo (control) groups. Varnishes were applied on permanent teeth once a week for the first 4 weeks and after the 6 th and 12 th months of the study. The variables were as follows: Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In 42 studies, 35.7% orthodontics WSLs, 4.8% non-orthodontics WSLs, 16.7% WSLs without special introductions, 7.1% ACLs,19.0% ECLs, 2.4% molar incisor hypo-mineralization (MIH) [ 75 ] and 14.3% artificial lesions compose all lesions. But a single ACL study with a description of ICDAS = 2 resulted in its inclusion in NMA [ 68 ]. Due to the uncertainty of using fluoride toothpaste in oral education (Some articles have explicit descriptions, others do not), we did not consider the efficacy of fluoride toothpaste in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In 42 studies, 35.7% orthodontics WSLs, 4.8% non-orthodontics WSLs, 16.7% WSLs without special introductions, 7.1% ACLs,19.0% ECLs, 2.4% molar incisor hypo-mineralization (MIH) [ 75 ] and 14.3% artificial lesions compose all lesions. But a single ACL study with a description of ICDAS = 2 resulted in its inclusion in NMA [ 68 ]. Due to the uncertainty of using fluoride toothpaste in oral education (Some articles have explicit descriptions, others do not), we did not consider the efficacy of fluoride toothpaste in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Various forms of fluoride, including NaF gel, NaF-HF gel, APF gel, APF foam, Na FV, titanium tetra FV, and SDF, were utilized in these studies. Among the 13 studies, 7 reported a significant reduction in new caries development on permanent teeth with the use of professionally applied fluorides compared with a placebo or no treatment (p < 0.05) [31][32][33][46][47][48][49]. However, the remaining six studies did not find a statistically significant difference (p > 0.05) [50,51].…”
Section: Effectiveness Of the Professionally Applied Fluorides Based ...mentioning
confidence: 99%